1996
DOI: 10.1021/ie950363l
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Polynuclear Aromatic Hydrocarbons in Water. 3. UV Radiation Combined with Hydrogen Peroxide

Abstract: Oxidation in water of three polynuclear aromatic hydrocarbons (PAHs), fluorene, phenanthrene, and acenaphthene, with UV radiation combined with hydrogen peroxide has been studied. The effect of hydrogen peroxide concentration, pH, and bicarbonate ion has been investigated. Disappearance rates of PAHs are substantially increased with respect to those from UV radiation alone if proper conditions of hydrogen peroxide concentration and pH are established. Direct photolysis contribution decreases with the increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 24 publications
8
48
0
Order By: Relevance
“…3). This is in agreement with the observations of Beltran et al [1996] and Stefan et al [1996] that direct photolysis contributions decreased when the pH is increased from 3 to 7.…”
Section: Optimization Of Initial Phsupporting
confidence: 93%
“…3). This is in agreement with the observations of Beltran et al [1996] and Stefan et al [1996] that direct photolysis contributions decreased when the pH is increased from 3 to 7.…”
Section: Optimization Of Initial Phsupporting
confidence: 93%
“…Therefore, the optimum peroxide dose was 50 mg L −1 under the experimental conditions used. In agreement with Glaze et al [26] and Beltran et al [27], a reduction in TOC removal was observed at high peroxide concentrations indicating the adverse effects of excess peroxide doses. This is due to hydroxyl ion (HO • ) scavenging by excess H 2 O 2 and consequent formation of the less reactive radical HO 2…”
Section: Toc Removal: Mineralization Of Simazinesupporting
confidence: 89%
“…(3) become stronger. Hence, the oxidation rate is reduced as compared to acidic or neutral pH levels [18]. No significant difference in the OH radical oxidation rate of IMP was obtained between pH values of 4 and 7, as shown in Fig.…”
Section: Imp Photolysismentioning
confidence: 75%